Intercultural citizenship education in the English language classroom in higher education: Does it lead to language learning? - Porto, Melina (2016)
This paper reports a bilateral university project in the foreign language classroom designed to promote intercultural competence, language development and active and responsible citizenship through content-language integrated learning (CLIL). The rationale for broadening the scope of language courses and combining them with intercultural citizenship or human rights education rests on the idea that language teaching has instrumental (linguistic-oriented and communicative) purposes as well as educational purposes (development of critical thinking skills, development of the self and of the citizenship dimension) (Byram, 2014). Pedagogic proposals (Porto, 2015) and empirical studies reporting on classroom practice are recently available (Byram, Golubeva, Han & Wagner, 2016; Porto, 2014; Porto & Byram, 2015b). These studies have connected both types of education (language and citizenship/human rights) and have demonstrated growth in self/intercultural awareness, criticality and social justice responsibility, as well as the emergence of a sense of community among students during the projects. However, the concern remains as to whether this combination leads to language learning and this article addresses this issue.